Bringing art and culture to community: Kota Tinggi Art Gallery - Muhammad Zulhilmi Mohd Radzi, 1995-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Project Paper (Sarjana Muda Sains (Pembinaan)) - Universiti Teknologi Malaysia, 2019